Design And Development of Gens (Google Sites Fun Physics) Integrated with Artificial Intelligence as An Innovative Physics Learning Platform to Improve Conceptual Mastery - Musdar Musdar; Ismail Ismail (Postgraduate, University of Mataram, 2026)
The development of the GENS (Google Sites Fun Physics) media integrated with artificial intelligence to improve concept understanding aims to develop learning media that meets the criteria of feasibility, namely valid, practical, and effective. The research was conducted at SMA Negeri 1 Tinambung with the research subjects being class X.6, comprising a sample of 32 students in the first semester of 2025/2026. Based on the analysis results, the Google Sites fun physics learning media is in the very valid category with a percentage of 90.8%, as measured by expert validator assessments. It is also in the very practical category with a cumulative percentage of 89.72%, based on student response assessments of 83.74% and teacher responses of 95.71%. The media is in the effective category with a moderate level and an N-gain value of 0.6. Therefore, it is recommended that physics teachers use the Google Sites Fun Physics learning media integrated with artificial intelligence to improve students' understanding of physics concepts.